Open Access publishing as a bridge across the digital divide - Saariluoma, Pertti (Human Technology, 2007)
In today’s world of snappy catchphrases, the complexity of a phenomenon is often hidden behind the simplicity of the terminology. Take, for instance, the concept of the digital divide. In short, the term means that there is a gap between those people who have effective access to digital technologies (and all the benefits that brings) and those who do not (Organization for Economic Cooperation and Development [OECD], 2001; Selhofer & Hüsing, 2002). While the definition seems simple enough, in fact, there are numerous reasons for the technology gap among people in the world. Typical reasons for the digital divide include material access (i.e., no access to a computer, lack of access to specific software programs or related technologies), usability or usage access (i.e., lack of qualified instruction or environmental issues that limit access, such as an erratic electrical power supply or an underdeveloped Internet infrastructure), or mental access (i.e., a lack of digital experience resulting from disinterest or computer anxiety; Van Dijk & Hacker, 2003). Because the digital divide is such a complex phenomenon, it needs a complex approach to bridging this gap. A multilayered approach to address this multifaceted problem has been proposed by both individuals and organizations (Arunachalam, 2003; Oyebode, 2002; Papin-Ramcharan & Dawe, 2006).